Article XXIV and world trading system - Skider, Mohammad Mashooqur Rahman (KDI School, 2011)
The WTO is a member driven organization, as of April 2011 it has 153 members. The main objective of WTO is liberalizing the trade around the world and become the catalyst of multilateral trading system. Accordingly, GATT/WTO is governed with the spirit of non discrimination rule or Most-Favoured Nations (MFN) treatment to all members but exceptions remain in non-discrimination rules. GATT Article XXIV of 1947, Enabling Clause, 1979 and GATS Article V are prime examples of MFN exceptions. Using the scope of these articles contracting parties/members states are forming Regional Trading Arrangements (RTAs).It’s quite alarming that Preferential tariff Agreements in the form of Custom Union(CU), forming Free Trade Agreement (FTA), more closure in terms of Economic Integration Agreement (EIA) as well as Partial Scope Agreement (PS) are being concluded around the world. As of July 2010 there are 283 RTAs have been notified to the Secretariat and which are actively enforced by the parties. Thus RTAs under exception clauses become the salient feature of the Multilateral trading systems with its cross regional and hub- spokes dimensions. All these are being happened under the rules and regulations of agreed agreements but in some cases contracting parties/members are exercising beyond that of Agreements. As a result there are lots of deviations from GATT/WTO non-discrimination principle MFN and others. Henceforth question arises “Does the Article XXIV serve the World trading system? Eventually this is the thesis question as well. This paper will examine the answer of thesis question with discussion on the historical pursuit and the scope of Article XXIV or related articles mentioned by different authorities, describing the oversight functions of Working Party or Committee on Regional Trade Agreement of GATT/WTO, legal implications of article XXIV and related or relevant decisions of Contracting Parties, Panel and Appellate body in DSB case on disputes under article XXIV. Finally, development of the current Doha Round negotiations and its dimension related to RTA rules will also be reflected in this paper.
Thesis(Master) --KDI School:Master of Public Policy,2011